2007
DOI: 10.1024/0300-9831.77.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astaxanthin Supplementation on Lipid Peroxidation

Abstract: Astaxanthin, the main carotenoid pigment in aquatic animals, has greater antioxidant activity in vitro (protecting against lipid peroxidation) and a more polar configuration than other carotenoids. We investigated the effect of three-month astaxanthin supplementation on lipid peroxidation in healthy non-smoking Finnish men, aged 19-33 years by using a randomized double-blind study design. Also absorption of astaxanthin from capsules into bloodstream and its safety were evaluated. The intervention group receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 5 publications
3
60
1
Order By: Relevance
“…In the present study, the elevated levels of MDA in tissues and erythrocyte membrane are consistent with earlier reports [26] . Treatment with carotenoids reduced the levels of MDA to near normal, which could be associated with its protective role.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, the elevated levels of MDA in tissues and erythrocyte membrane are consistent with earlier reports [26] . Treatment with carotenoids reduced the levels of MDA to near normal, which could be associated with its protective role.…”
Section: Discussionsupporting
confidence: 82%
“…Astaxanthin is distributed primarily in marine organisms, and is isolated from the algae Haematococcus pluvials [6]. Clinical studies have confirmed that astaxanthin has significant effects on lipid peroxidation and inflammation, as well as functional dyspepsia and male infertility [7][8][9][10]. Additionally, astaxanthin has been reported to improve lipid metabolism in animal models and humans with dyslipidemia.…”
Section: Introductionmentioning
confidence: 94%
“…The green microalga, Haematococcus pluvialis Flotow (Chlorophyceae), is considered to be the richest natural source of astaxanthin for pharmaceutical, nutraceutical, and cosmetics applications due to its high antioxidant activities and for the aquaculture and poultry industries due to its impact on animal pigmentation (Miki 1991, Nishino 1998, Kobayashi 2000, Guerin et al 2003, Karppi et al 2007. Mass cultivation of H. pluvialis for commercial purposes has been exploited in both open ponds (Johnson andAn 1991, Zhang et al 2009) and closed photobioreactors of various designs since the 1990's (Lorenz andCysewski 2000, Han et al 2013).…”
Section: Introductionmentioning
confidence: 99%